A novel founder MYO15A frameshift duplication is the major cause of genetic hearing loss in Oman - Palombo, Flavia; Al-Wardy, Nadia; Ruscone, Guido Alberto Gnecchi; Oppo, Manuela; Kindi, Mohammed Nasser Al; Angius, Andrea; Al Lamki, Khalsa; Girotto, Giorgia; Giangregorio, Tania; Benelli, Matteo; Magi, Alberto; Seri, Marco; et al. (Journal of human genetics, 2017)
The increased risk for autosomal recessive disorders is one of the most well-known medical implications of consanguinity. In the Sultanate of Oman, a country characterized by one of the highest rates of consanguineous marriages worldwide, prevalence of genetic hearing loss (GHL) is estimated to be 6/10 000. Families of GHL patients have higher consanguinity rates than the general Omani population, indicating a major role for recessive forms. Mutations in GJB2, the most commonly mutated GHL gene, have been sporadically described. We collected 97 DNA samples of GHL probands, affected/unaffected siblings and parents from 26 Omani consanguineous families. Analyzing a first family by whole-exome sequencing, we identified a novel homozygous frameshift duplication (c.1171_1177dupGCCATCT) in MYO15A, the gene linked to the deafness locus DFNB3. This duplication was then found in a total of 8/26 (28%) families, within a 849 kb founder haplotype. Reconstruction of haplotype structure at MYO15A surrounding genomic regions indicated that the founder haplotype branched out in the past two to three centuries from a haplotype present worldwide. The MYO15A duplication emerges as the major cause of GHL in Oman. These findings have major implications for the design of GHL diagnosis and prevention policies in Oman.